(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Historically, empirical studies of the education production function have looked at howteachers and the personal traits they bring to the classroom affect their students’ results onstandardised tests. But a large body of data indicates that learning is multidimensional, with manyaspects other than a student’s basic academic knowledge as major contributors to both short-term andlong-term success. Despite the fact that fundamental academic knowledge has a role in developingstudent’s learning. Thus, this paper aims to analyse the existing literature related to student’sdevelopment and teachers’ role in their wholistic development